2011
DOI: 10.1088/0004-637x/731/1/53
|View full text |Cite
|
Sign up to set email alerts
|

PRELIMINARY RESULTS FROM NEOWISE: AN ENHANCEMENT TO THEWIDE-FIELD INFRARED SURVEY EXPLORERFOR SOLAR SYSTEM SCIENCE

Abstract: The Wide-field Infrared Survey Explorer has surveyed the entire sky at four infrared wavelengths with greatly improved sensitivity and spatial resolution compared to its predecessors, the Infrared Astronomical Satellite and the Cosmic

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
492
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 735 publications
(500 citation statements)
references
References 68 publications
7
492
0
1
Order By: Relevance
“…The neutral to moderately red slopes, 0%-3% per 0.1 μm, are potentially the most consistent with the suggested Q or V spectral types. The chosen range of η is based on the distribution of beaming parameters in WISE observations of near-Earth objects (Mainzer et al 2011). For each combination of S and η, we let diameter, D, and geometric albedo, A p , vary freely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutral to moderately red slopes, 0%-3% per 0.1 μm, are potentially the most consistent with the suggested Q or V spectral types. The chosen range of η is based on the distribution of beaming parameters in WISE observations of near-Earth objects (Mainzer et al 2011). For each combination of S and η, we let diameter, D, and geometric albedo, A p , vary freely.…”
Section: Resultsmentioning
confidence: 99%
“…Most do not display a coma or tail; however, these "sporadic" objects are designated as comets since all prior objects seen at these distances have been of apparently cometary origin. This assumption is reasonable given that SOHOʼs limiting magnitude would necessitate a bare asteroid being 10 km in diameter to be observed; numerous such large objects are unlikely to be missed in the modern survey era, especially by NEOWISE where they would be particularly bright (Mainzer et al 2011). Although these objects are almost certainly active when in the SOHO fields of view (0.15 au), this activity is not necessarily due to the traditional "cometary" mechanism of sublimation of volatile ices.…”
Section: Introductionmentioning
confidence: 99%
“…In the Southern sky (δ < −20 • ), there is very little SDSS data. Nevertheless, the availability and coverage of the AllWISE catalogue (Mainzer et al 2011) allows us to use period and colour information to broadly separate distinct types of variability.…”
Section: Discussionmentioning
confidence: 99%
“…The approximate flux limits of the AO13 portion of the Stripe 82X survey are 2.2×10 −15 erg s −1 cm −2 , 1.3×10 −14 erg s −1 cm −2 , and 6.7×10 −15 erg s −1 cm −2 , in the soft (0.5-2 keV), hard (2-10 keV), and full (0.5-10 keV) bands. From matching the X-ray source list to available multiwavelength catalogs, including SDSS (Ahn et al 2012;Jiang et al 2014), WISE (Wright et al 2010;Mainzer et al 2011), UKIDSS (Hewett et al 2006;Casali et al 2007;Lawrence et al 2007;Warren et al 2007), VHS (McMahon et al 2013), GALEX (Morrissey et al 2007), FIRST Helfand et al 2015), and Herschel (Viero et al 2014), we identified reliable counterparts for 93% of the sample. About 29% of the X-ray sources are classified via spectroscopic redshifts.…”
Section: Resultsmentioning
confidence: 95%
“…Since publishing our initial Stripe 82X multi-wavelength matched catalogs in LaMassa et al (2013a), the AllWISE Source Catalog was released, combining data from the cryogenic and NEOWISE missions (Wright et al 2010;Mainzer et al 2011). As this catalog has enhanced sensitivity and astrometric precision, we match the XMM-Newton AO13 X-ray source list to this release, and update the archival Chandra and XMM-Newton and XMM-Newton AO10 matches to AllWISE, as detailed in the appendix.…”
Section: Wisementioning
confidence: 99%